2021
DOI: 10.3390/fib9120088
|View full text |Cite
|
Sign up to set email alerts
|

Impact Resistance of Functionally Layered Two-Stage Fibrous Concrete

Abstract: The impact resistance of functionally layered two-stage fibrous concrete (FLTSFC) prepared using the cement grout injection technique was examined in this study. The impact resistance of turtle shells served as the inspiration for the development of FLTSFC. Steel and polypropylene fibres are used in more significant quantities than usual in the outer layers of FLTSFC, resulting in significantly improved impact resistance. An experiment was carried out simultaneously to assess the efficacy of one-layered and tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…The use of this material can increase the tensile strength of the cement matrix, allowing a cement concrete of higher flexural strength to be obtained [ 21 ]. It is recommended to use polypropylene fiber in the technology of fiber concrete to reduce the delamination of mixtures, increase water resistance, frost resistance, corrosion resistance, and impact strength, and reduce abrasion [ 2 , 22 ]. In addition, polypropylene fiber is characterized by corrosion resistance in various environments [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of this material can increase the tensile strength of the cement matrix, allowing a cement concrete of higher flexural strength to be obtained [ 21 ]. It is recommended to use polypropylene fiber in the technology of fiber concrete to reduce the delamination of mixtures, increase water resistance, frost resistance, corrosion resistance, and impact strength, and reduce abrasion [ 2 , 22 ]. In addition, polypropylene fiber is characterized by corrosion resistance in various environments [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The p -values of the obtained impact results (based on the Kolmogorov–Smirnov test) showed that these results hardly followed the normal distribution. Murali et al [ 49 ] conducted repeated impact tests on concrete specimens that included green substitutions to cement and fine aggregate, where two identical mixtures were prepared with or without 0.5% of 50 mm length hooked-end SF. The cement was partially replaced with 2% of nano silica, while 30% of the fine aggregate was replaced with copper slag.…”
Section: Previous Literature On the Statistical Evaluation Of Aci 544...mentioning
confidence: 99%
“…However, comparing the results presented by the authors, it is clear that on average, for all mixtures, the case with line notch and sand bedding resulted in the best scattering reduction results, where the percentage reduction in the COV was in the range of 58 to 66% for the five mixtures, which supports the results of Abid et al [ 69 ]. Murali et al [ 49 ] tested the impact resistance of eleven functionally graded, preplaced concrete mixtures reinforced with hybrid steel–polypropylene fibers using the line notched specimens and line load-transferring plate. Fifteen specimens were tested from each mixture, and seriously low COV values of 5.9 to 16.6% were reported.…”
Section: Suggested Modifications To the Aci 544-2r Repeated Impact Testmentioning
confidence: 99%
See 1 more Smart Citation
“…This method was used to create fiber reinforced concrete (FRC) in the 20th century, which gained popularity in the building sector because of its increased strength. Steel fiber incorporation in the cement matrix improves the toughness, yield load, first cracking load, moment of resistance, and crack resistance of reinforced concrete beams subjected to transverse loading, according to research on fiber-reinforced concrete [54][55][56][57][58][59][60]. The improvement in the ductility for fiber addition, on the other hand, is a critical characteristic for structural concrete members.…”
Section: Introductionmentioning
confidence: 99%